Women in tech : a perfect fit for a sustainable and inclusive future /. - Jacobs, Laurence, ....- (Kalmthout : Pelckmans, 2023)
Women in Tech: A Perfect Fit for a Sustainable and Inclusive Future explores the persistent challenge of attracting, advancing and retaining women in the technology industry. Despite making up more than half of the global population, women represent only a quarter of the workforce in the technology industry. This insightful book presents five key strategies to address this disparity, including the importance of digital skills, representation and role models, cultivating inclusive company cultures, providing access to funding for female founders and inspiring the next generation in STEM fields. With interviews featuring inspirational women and men, real-life company cases and role models, this comprehensive guide provides a valuable resource for promoting gender equality in the tech sector. It also showcases organisations and experts who are actively pursuing a more diverse and inclusive tech industry. Whether you work in the technology field or are committed to promoting diversity and inclusion, Women in Tech offers useful insights and practical tools to drive meaningful change.
Keywords: Arbeidsverdeling; STEM; Sekseverschillen; Technologie en vrouwen